Suppression of autophagy promotes fibroblast activation in p53-deficient colorectal cancer cells - Takanori Inoue (Nature Portfolio, 2021)
Abstract Deficiency of p53 in cancer cells activates the transformation of normal tissue fibroblasts into carcinoma-associated fibroblasts; this promotes tumor progression through a variety of mechanisms in the tumor microenvironment. The role of autophagy in carcinoma-associated fibroblasts in tumor progression has not been elucidated. We aimed to clarify the significance of autophagy in fibroblasts, focusing on the TP53 status in co-cultured human colorectal cancer cell lines (TP53-wild-type colon cancer, HCT116; TP53-mutant colon cancer, HT29; fibroblast, CCD-18Co) in vitro. Autophagy in fibroblasts was significantly suppressed in association with ACTA2, CXCL12, TGFβ1, VEGFA, FGF2, and PDGFRA mRNA levels, when co-cultured with p53-deficient HCT116 sh p53 cells. Exosomes isolated from the culture media of HCT116 sh p53 cells significantly suppressed autophagy in fibroblasts via inhibition of ATG2B. Exosomes derived from TP53-mutant HT29 cells also suppressed autophagy in fibroblasts. miR-4534, extracted from the exosomes of HCT116 sh p53 cells, suppressed ATG2B in fibroblasts. In conclusion, a loss of p53 function in colon cancer cells promotes the activation of surrounding fibroblasts through the suppression of autophagy. Exosomal miRNAs derived from cancer cells may play a pivotal role in the suppression of autophagy.